2007
DOI: 10.1152/ajpendo.00605.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to a low-protein diet programs disordered regulation of lipid metabolism in the aging rat

Abstract: Erhuma A, Salter AM, Sculley DV, Langley-Evans SC, Bennett AJ. Prenatal exposure to a low-protein diet programs disordered regulation of lipid metabolism in the aging rat. Am J Physiol Endocrinol Metab 292: E1702-E1714, 2007. First published February 13, 2007; doi:10.1152/ajpendo.00605.2006.-The nutritional environment encountered during fetal life is strongly implicated as a determinant of lifelong metabolic capacity and risk of disease. Pregnant rats were fed a control or low-protein (LP) diet, targeted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
143
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 42 publications
12
143
2
2
Order By: Relevance
“…Fatty liver can ultimately lead to inflammation and scarring (Erhuma et al 2007). Although this condition has multiple causes, fatty liver is a pathological condition in which triglyceride fats accumulate within hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty liver can ultimately lead to inflammation and scarring (Erhuma et al 2007). Although this condition has multiple causes, fatty liver is a pathological condition in which triglyceride fats accumulate within hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have indeed demonstrated that infants born small for gestational age are more prone to develop obesity, hypertension and type 2 diabetes in adulthood. [27][28][29] Experimental studies have further corroborated that rodents and other animal species submitted to protein or calorie restriction during gestation and/or suckling exhibit hyperphagia, [30][31][32][33] insulin resistance, 34,35 reduced leptin sensitivity, 36,37 hepatic steatosis, 38 elevated blood pressure 39,40 and hyperlipidemia. 35,37,38 These observations have been explained by the thrifty phenotype hypothesis, also called metabolic programming or the developmental origins of disease.…”
Section: Introductionmentioning
confidence: 93%
“…[27][28][29] Experimental studies have further corroborated that rodents and other animal species submitted to protein or calorie restriction during gestation and/or suckling exhibit hyperphagia, [30][31][32][33] insulin resistance, 34,35 reduced leptin sensitivity, 36,37 hepatic steatosis, 38 elevated blood pressure 39,40 and hyperlipidemia. 35,37,38 These observations have been explained by the thrifty phenotype hypothesis, also called metabolic programming or the developmental origins of disease. [41][42][43][44][45] It is hypothesized that perinatal undernutrition sensitizes the offspring to the development of metabolic diseases via epigenetic changes that act during early life to program feeding behavior and energy homeostasis for optimal survival under nutritionallydeficient conditions.…”
Section: Introductionmentioning
confidence: 93%
“…There is also evidence of resistance to adiposity during early adult life. However, as the animals age they develop a progressive insulin resistance, and overexpression of lipogenic pathways in the liver results in profound hepatic steatosis when compared with controls of the same age (52,53) . Feeding behaviour is programmed by maternal protein restriction, which appears to suggest that undernutrition in fetal life impacts upon the development of the hypothalamus (54,55) .…”
Section: Animal Models Of Nutritional Programmingmentioning
confidence: 99%